DECOLORIZATION OF TEXTILE EFFLUENTS CONTAINING REACTIVE DYES USING THE ELECTRO-OXIDATION METHOD WITH TITANIUM ELECTRODES - Cárdenas Mendoza, Teodardo J. (2023)
In this research, the electro-oxidation method was applied to decolorize real and simulated effluents from cotton dyeing processes with reactive dyes, this method was applied using mesh type electrodes, the titanium cathode and the titanium anode coated with ruthenium and iridium. Two types of reactors were used, one-compartment and separated double-compartment with exchange membrane, to compare the electrochemical performance in the decolorization of textile effluents containing reactive dyes (Corafix Blue Mers 150%, Corafix Golden Yellow Mer 150% and Corafix Red Me-4B 150%). During discoloration tests, the dye and chlorine content was monitored using UV-visible spectrophotometry. In the laboratory tests, the simulated effluent was treated at a concentration of 300 mg/L of red dye, with the two-compartment reactor being more efficient with 95.9% decolorization. In the pilot tests, 99.1% of the real effluent was decolorized. Finally, the real treated effluent was reused in a dyeing test, obtaining acceptable color results in the textile industry.